ECONOMIC FEASIBILITY OF HEATING SOURCE CONVERSION OF THE SWIMMING POOLS - Al-Falahat, Ala'a; Abu Qadourah, Jenan; Alrwashdeh, Saad (Journal of Applied Engineering Science, 2022)
Conversion from conventional heating systems is developed to address the emission of CO2 in the environment, global warming, rising costs, potential shortages of fossil fuels, for all energy source alternatives available. This study reviewed the economic feasibility associated with converting the current heat source to a renewable energy source of heating swimming pools located in Jordan. Many modern heating systems techniques are proposed in this study such as solar heat collectors, heat pump and photovoltaic assisted heat pump. Solar heat collectors are a device that collects and/or concentrate solar radiation from the sun and allow for heating the water. In addition, a growing interest in photovoltaic/heat pump systems is considered, which combines photovoltaic cells and heat pump systems. Hence converting solar energy into electricity and then heat through the heat pump. The Initial and operation cost for all proposed techniques is evaluated. As a result, it is found that the best economical alternative option that can be installed on the available area of the building is photovoltaic with a heat pump system during the heating season. The operation cost of the current source (diesel boiler) is about 179,974 US$ and the total cost of heat solar thermal collector is about 936,540 US$ but the total cost of the proposed photovoltaic/heat pump system is nearly 251,060 US$, which save about 45,134 US$ yearly of the total commercial building electricity bill that is selected with a payback period of fewer than two years. In addition, available space on the rooftop of the selected building is well fitted with photovoltaic panels which are around 2000 m2. This result suggests that utilizing a PV/HP system for hotel pools is advantageous both financially and environmentally.
Keywords: conventional heating source, economic feasibility, swimming pool, photovoltaic/heat pump